(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The increased interest in the study of the Russian language in China stimulates the interest of Chinese teachers of Russian language to educational and methodological materials created by Russian colleagues. First of all, Uzbek Russianists are interested in nationally-oriented textbooks. This article discusses the features presentation of grammar in Russian textbooks aimed at foreign students, only beginners to learn Russian language.